A coordinated cross‐disciplinary research initiative to address an increased incidence of narcolepsy following the 2009–2010 Pandemrix vaccination programme in Sweden. (30th June 2015) - Feltelius, N.; Persson, I.; Ahlqvist‐Rastad, J.; Andersson, M.; Arnheim‐Dahlström, L.; Bergman, P.; Granath, F.; Adori, C.; Hökfelt, T.; Kühlmann‐Berenzon, S.; Liljeström, P.; Maeurer, M.; et al.
Abstract In response to the 2009–2010 influenza A(H1N1)pdm09 pandemic, a mass vaccination programme with the AS03‐adjuvanted influenza A(H1N1) vaccine Pandemrix was initiated in Sweden. Unexpectedly, there were a number of narcolepsy cases amongst vaccinated children and adolescents reported. In this review, we summarize the results of a joint cross‐disciplinary national research effort to investigate the adverse reaction signal from the spontaneous reporting system and to better understand possible causative mechanisms. A three‐ to fourfold increased risk of narcolepsy in vaccinated children and adolescents was verified by epidemiological studies. Of importance, no risk increase was observed for the other neurological and autoimmune diseases studied. Genetic studies confirmed the association with the allele HLA‐DQB1*06:02, which is known to be related to sporadic narcolepsy. Furthermore, a number of studies using cellular and molecular experimental models investigated possible links between influenza vaccination and narcolepsy. Serum analysis, using a peptide microarray platform, showed that individuals who received Pandemrix exhibited a different epitope reactivity pattern to neuraminidase and haemagglutinin, as compared to individuals who were infected with H1N1. Patients with narcolepsy were also found to have increased levels of interferon‐gamma production in response to streptococcus‐associated antigens. The chain of patient‐related events and the study results emerging over time were subjected to intense nationwide media attention. The importance of transparent communication and collaboration with patient representatives to maintain public trust in vaccination programmes is also discussed in the review. Organizational challenges due to this unexpected event delayed the initiation of some of the research projects, still the main objectives of this joint, cross‐disciplinary research effort were reached, and important insights were acquired for future, similar situations in which a fast and effective task force may be required to evaluate vaccination‐related adverse events.